IS CRIMEAN-CONGO HEMORRHAGIC FEVER VIRUS TOPOTYPE IMPORTANT IN THE POSSIBILITY OF NOSOCOMIAL TRANSMISSION? - YAĞÇI ÇAĞLAYIK, DİLEK (CARBONE EDITORE, 2017)
Introduction: Crimean-Congo hemorrhagic fever (CCHF) is a viral zoonotic disease which is mainly transmitted by tick bite. Contact with blood or body secretions of viremic humans or animals is also among the other modes of transmission. In this study, the serological states in terms of CCHF tested in healthcare workers (HCW) who had had contact with two fatal patients with a diagnosis of CCHF. The relation of the transmission possibility with the phylogenetic analysis of the virus were evaluated. Materials and methods: CCHF IgM and IgG were investigated with ELISA one month after contact with index cases in HCW. The contact levels and states of use of personal protective equipment (PPE) were evaluated. Phylogenetic analysis with sequence analysis based on partial sequences of NP coding region was performed for CCHF viruses detected in the index cases. Results: CCHF IgM and IgG were found negative in any of 20 healthcare workers some of whom had a history of high-risk contact. The sequence analysis revealed that the viruses found in both patients were identical. Phylogenetic evaluation showed that both viruses have high homology with the viruses which were determined previously in the endemic area in Turkey. Conclusion: As in our study, detection of virus topotype with sequence analysis in studies about nosocomial transmission will help to determine if there is a difference between virus subtypes in terms of transmission.
Keywords: Crimean-Congo hemorrhagic fever; nosocomial transmission; Phylogenetic analysis; M-RNA SEGMENT; RIBAVIRIN PROPHYLAXIS; OUTBREAK